2006
DOI: 10.1177/2156759x0601000207
|View full text |Cite
|
Sign up to set email alerts
|

Career and College Planning Needs of Ninth Graders–as Reported by Ninth Graders

Abstract: Few researchers have asked students directly about what they know and need to know regarding college and career planning. Given the critical choices made early in high school, ninth graders (n = 222) were surveyed regarding their educational and career plans and the resources they were using in their decision-making. Overall results as well as differences by ethnicity, gender, and parent education group are reported. Results indicated a discrepancy between plans and accurate information about college costs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 13 publications
4
20
0
Order By: Relevance
“…Many PFGCSs benefit from additional support DECEMBER 2019 • VOLUME 67 for college-going because they are less likely to have had role models, such as relatives, family friends, or other community members, who attended college. Additionally, previous research indicates that PFGCSs, compared with their non-first-generation peers, tend to rate themselves lower academically and are more likely to endorse plans to enter the workforce directly after high school (Gibbons, Borders, Wiles, Stephan, & Davis, 2006). Furthermore, FGCSs demonstrate lower educational expectations and aspirations and are less likely to choose a STEMM major (Chen, 2005) than students whose parents attended college.…”
Section: Rural Appalachian Studentsmentioning
confidence: 99%
“…Many PFGCSs benefit from additional support DECEMBER 2019 • VOLUME 67 for college-going because they are less likely to have had role models, such as relatives, family friends, or other community members, who attended college. Additionally, previous research indicates that PFGCSs, compared with their non-first-generation peers, tend to rate themselves lower academically and are more likely to endorse plans to enter the workforce directly after high school (Gibbons, Borders, Wiles, Stephan, & Davis, 2006). Furthermore, FGCSs demonstrate lower educational expectations and aspirations and are less likely to choose a STEMM major (Chen, 2005) than students whose parents attended college.…”
Section: Rural Appalachian Studentsmentioning
confidence: 99%
“…High school students indicate they want information about and exposure to different careers, as well as assistance in choosing a career (Gibbons et al 2006). Previous research has found students identify teachers as helpful and influential in their career decision-making process (Gibbons et al 2006;Kniveton 2004;Paa and McWhirter 2000).…”
Section: Introductionmentioning
confidence: 99%
“…High school students indicate they want information about and exposure to different careers, as well as assistance in choosing a career (Gibbons et al 2006). Previous research has found students identify teachers as helpful and influential in their career decision-making process (Gibbons et al 2006;Kniveton 2004;Paa and McWhirter 2000). Additionally, parents perceive teachers as a career resource for students and rely on teachers to guide their children in career preparation and planning (Gibbons et al 2006;Trusty and Watts 1996).…”
Section: Introductionmentioning
confidence: 99%
“…For persistence beliefs (15-30), school counselors can focus on ability (items 16, 20, 21, 25, 28, 30), finances (items 15, 20), family responsibilities (items 17, 22), life skills (items 18, 23, 24, 26, 29), and general feelings about continuing in college (items 19, 27). Students who score low on the financially related questions can be given concrete information about the actual costs of college, because students tend to overestimate these costs (Gibbons et al, 2006). Similar interventions could target other belief categories.…”
Section: Implications For School Counselorsmentioning
confidence: 99%